Our World's Fair - V. Toutjean Jr.::::::::: (Toutjean & Childers)
Piano and vocal score, 5 p. On cover: Respectfully dedicated to the Nineteen Thirty Nine [sic] International Exposition, Treasure Island, San Francisco Bay.